PCDH9 suppresses melanoma proliferation and cell migration - Zhang, Jiaojiao; Yang, Hui-Zhi; Liu, Shuang; Islam, Md Obaidul; Zhu, Yue; Wang, Zuhua; Chen, RongYi (Frontiers in Oncology, 2022)
Background Melanoma has dramatically increased during last 30 years with low 5-year survival and prognosis rate. Methods Melanoma cells (A375 and G361) were chosen as the in vitro model. The immunohistochemical (IHC) analysis and bioinformatics mining exhibited the suppression of PCDH9 on melanoma. The interference and overexpression of PCDH9 were infected by lentivirus. The effects of PCDH9 on melanoma cells were assessed in terms of alteration of PCDH9 such as cell viability, apoptosis, cell cycle, and wound-healing assay. Moreover, expressions of PCDH9 with other genes (MMP2, MMP9, CCND1, and RAC1) were also assessed by PCR. Results The alteration of PCDH9 has a negative correlation with MMP2, MMP9, and RAC1 but had a positive correlation with CCND1 (Cyclin D1) and apoptosis. Increase of PCDH9 could suppress melanoma cells and inhibit migration but not exert significant effects on cell cycle. IHC showed lower PCDH9 expression in melanoma tissue with main expression in cytoplasm. Conclusion Overexpressed PCDH9 suppressed melanoma cells, and PCDH9 can be considered as an independent prognostic factor for melanoma; even re-expression of PCDH9 can serve as a potential therapeutic strategy for melanoma treatment.